ChemInform Abstract: Metal‐Free Visible‐Light Induced Cross‐Dehydrogenative Coupling of Tertiary Amines with Diazo Compounds. Issue 7 (29th January 2015) - Xiao, Tiebo; Li, Linyong; Lin, Guoliang; Mao, Zong‐wan; Zhou, Lei
Abstract The title reaction proceeds under mild and metal‐free conditions, affording β‐amino‐α‐diazo adducts by using air or oxygen as oxidant.